Expertskattereglerna – nya föreslagna förändringar. En analys av förändringarna och hur expertskattereglerna förhåller sig till de skatterättsliga principerna som vårt nuvarande skattesystem är uppbyggt på. - Dahlgren,Joel (2025)
A foreign individual who is considered an expert, researcher or otherwise an important person (nyckelperson) may currently be covered by what is commonly referred to as the expert tax rules (expertskattereglerna). Individuals who receive remuneration above a certain level are also subject to these rules. Under these rules, certain benefits qualify as tax-free as well as a part of the renumeration. The rules have historically been criticised for being unpredictable and difficult to apply. With respect to this, SOU 2025:3 presents a number of different proposals with the aim to address these issues. An example of this is the proposal of raising the tax-free level from 25 to 30 per cent and changing the so-called competence rule (kompetensregeln), as it is considered unpredictable and ineffective. No significant proposals is suggested for the so-called amount rule (beloppsregeln). However, the formal requirements are proposed to be lowered and, as a result, Swedish citizens should also be covered by the rules, the intention requirement (avsiktsregeln) should be abolished, the requirement for a Swedish employer should be retained and the residence requirement (vistelsekravet) is subject to change. Our current tax system was introduced in the early 1990s. It was preceded by extensive preparatory work and the reform has come to be known as the tax reform of the century. The reform was called for because the tax system at the time was perceived as inefficient and asymmetrical. As a result, the current tax system is intended to be neutral, uniform and in accordance with the principle of legitimacy. In conclusion; the proposed changes will, on the whole, more effectively meet the goals and objectives that the expert tax rules were originally intended to achieve, albeit not without certain problematic aspects. Nevertheless, the expert tax rules will continue to constitute an abnormality with respect to the principles of neutrality, uniformity and legitimacy.
Keywords: Skatterätt; Expertskattereglerna